Pengaruh Pendidikan, Pelatihan dan Pemahaman Akuntansi terhadap Kemampuan Mahasiswa Akuntansi Universitas 17 Agustus 1945 Surabaya dalam Mengerjakan Laporan Laba Rugi - Cailah Nasywa A.; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of education, training and understanding of accounting on the ability of accounting students at the University of 17 August 1945 Surabaya in preparing profit and loss reports. Through a qualitative approach, this research explores students' experiences in the accounting learning process and the challenges they face in applying this concept. Interviews were conducted with fifth semester accounting students who had received related education and training. The research results show that the majority of students feel that the process of preparing a profit and loss report is relatively easy, but challenges remain, especially in understanding accounting policies that frequently change and difficulties in managing complex information such as calculating taxes and cost of goods sold (COGS). The training provided is highly appreciated as it helps students develop analytical and practical skills, as well as deepening their understanding of accounting concepts. The combination of formal education and practical training has proven effective in improving students' ability to prepare financial reports accurately. It is hoped that this research can provide recommendations for developing curriculum and teaching methods in the field of accounting, so that students are better prepared to face the challenges of the world of work and are able to prepare financial reports properly and correctly.